Application of Measurement System Analysis (MSA) for Assesment of Tire Pressure Monitoring in Coal Mining Trucks - Hia, Selamat W. (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Tire pressure plays an important role in ensuring safe operation and performance of truck vehicles. Improper tire pressure always leads to tire life, vehicle safety, and performance. This paper discusses the application of measurement system analysis on truck tire pressure in a coal mining company. The study evaluates the measurement system of truck tire pressure. The company aims to extend the life span of its tire by maintaining and monitoring the tire pressure regularly. The tire pressure is measure by a pressure gauge. This study used measurement system analysis (MSA) to analyze the Gage R&R, with 2 tire men and 10 parts measured with 3 repetitions. The MSA results in a Total Gage R&R of 18.16% with a repeatability value of 12.34% and a reproducibility value of 13.32%. The result indicated that the measurement system showed good results for tire measurement applications because the Gage R&R was between 10% to 30%.